Priority Strategy of Financial Institution Pension Funds (FIPF) for Islamic Scheme in Indonesia: Internal, Market, and Regulation Approach - Jaenal Effendi (Global Review of Islamic Economics and Business, 2021)
According to a survey conducted by Otoritas Jasa Keuangan (OJK), 74.8% of workers and 85.7% of employers are attracted to Islamic pension funds. However, its market share is still relatively low compared to other Islamic financial product. The purpose of this study is to identify the internal, market and regulation issues that affect the development of FIPF (financial institution pension funds) and construct the strategy to develop FIPF for Islamic scheme. This study applies the analytical hierarchy process (AHP) to determine the strategy based on the priority scale assessed by several experts. The internal issues of FIPF are the priority of both problems and solutions in the development of FIPF for Islamic schemes. Furthermore, from the identification of problems and solutions, the strategy for optimizing FIPF scheme performance and services are the main strategies in expanding the FIPF’s market, followed by FIPF's socialization and literacy strategy, and strategies for strengthening relationships and synergy between the authority and FIPF management.